Qualitative analysis of histochemical and immunohistochemical properties of ethanol, glycerol, and formalin fixative - Buvaneswari V; Deepadevi G; Peter Samidoss A; Muthu Prabha MS; Vinoth Kumar V (Asian Journal of Medical Sciences)
Background: Fixation is essential in histopathology to preserve tissue integrity before analysis, with neutral buffered formalin being the gold standard for decades because of its effective protein cross-linking properties.